KONTRIBUSI HUTAN RAKYAT POLA AGROFORESTRY TERHADAP PENDAPATAN MASYARAKAT (Studi kasus : Desa Terong, Kecamatan Dlingo, Kabupaten Bantul, Provinsi Daerah Istimewa Yogyakarta) - Larasati, Hanim Nanda; Supriono, Bambang; Meiganati, Kustin Bintani (Jurnal Nusa Sylva, 2019)
Most community forests in the village of Terong apply agroforestry patterns to obtain contributions in the form of diverse crops each year, maintain forest sustainability, and be able to increase people's income in meeting their daily needs. This research was conducted to find out the management system and contribution of community forest agroforestry patterns in Terong Village. The data obtained is processed tabulation and analyzed descriptively qualitatively and quantitatively. The results of this study can be seen that the community forest management system of agroforestry patterns by the community in the village of Terong includes planning planting patterns and types of plants and several stages of agroforestry land development activities. The agroforestry pattern consists of trees along the border (barrier tree pattern), alley cropping (aisle pattern), alternate rows (row pattern), and random mixture (mixed patterns). Public forest agroforestry patterns in the village of Terong provide a significant contribution, which averages 75% of total community income. The highest contribution is in the random mixture pattern with a permanent time line and the constituent component uses multipurpose forest tree production.